PENDAMPINGAN SISWA OLEH KADER “GEMPI KESPRO” GENERASI MUDA PEDULI KESEHATAN REPRODUKSI DI SMPIT BINA INSANI KOTA KEDIRI - Erna Rahma Yani; Koekoeh Hardjito; Suwoyo Suwoyo (Universitas Kadiri, 2022)
Reproductive health issues are always an interesting topic of discussion among youth groups, including junior high school students. This community service activities aims to realize SMPIT Bina Insani Kediri as a school with a